Microglia autophagy in ischemic stroke: A double-edged sword - Peng, Li; Hu, Guangqiang; Yao, Qianfang; Wu, Jianming; He, Ziyang; Law, Betty Yuen-Kwan; Hu, Guishan; Zhou, Xiaogang; Du, Junrong; Wu, Anguo; Yu, Lu (Frontiers in Immunology, 2022)
Ischemic stroke (IS) is one of the major types of cerebrovascular diseases causing neurological morbidity and mortality worldwide. In the pathophysiological process of IS, microglia play a beneficial role in tissue repair. However, it could also cause cellular damage, consequently leading to cell death. Inflammation is characterized by the activation of microglia, and increasing evidence showed that autophagy interacts with inflammation through regulating correlative mediators and signaling pathways. In this paper, we summarized the beneficial and harmful effects of microglia in IS. In addition, we discussed the interplay between microglia autophagy and ischemic inflammation, as along with its application in the treatment of IS. We believe this could help to provide the theoretical references for further study into IS and treatments in the future.